Analisis Faktor-Faktor yang Mempengaruhi Auditor Switching di Indonesia Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Sri Mulyani Fahrin (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This research aims to analyze the factors that influence auditor switching in manufacturing companies. This research is quantitative research. The data used is secondary data from manufacturing company financial reports. The sample for this research is manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The sample selection method used was the purposive sampling method. The total sample for this research is 52 companies from 2017-2021 as the year of observation. The amount of data analyzed was 250 data. The analytical method used in this research is descriptive statistics and logistic regression testing using the SPSS Version 22 program. The results of the research show that audit opinion has an effect on auditor switching. Meanwhile, management changes and KAP size have no effect on auditor switching.